Integration of Health Fiqh Regarding Legal Aspects of Infectious Diseases in Handling The COVID-19 Pandemic - Nabilah Aprilia Marwa; Irwansyah Irwansyah; Nadia Amanda Azwa; Tria Syafira Matondang (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The Covid-19 pandemic has become a major challenge for humanity throughout the world. In handling this pandemic, the legal aspect of infectious diseases is an important aspect that needs to be considered. Health fiqh as a branch of fiqh which discusses health laws can contribute to handling the Covid-19 pandemic. The Covid-19 pandemic has become a big challenge for the world, including Indonesia. Handling this pandemic requires a comprehensive approach, including legal aspects. Health fiqh is a branch of fiqh that discusses laws relating to health, including infectious diseases. The integration of health fiqh in handling the Covid-19 pandemic can provide a strong legal framework that is in accordance with Islamic values. This research aims to examine the legal aspects of infectious diseases in handling the Covid-19 pandemic based on health fiqh. The research method used is a literature study with a qualitative approach. Data was obtained from various sources, including fiqh books, articles and journals. The research results show that health fiqh has an important role in handling the Covid-19 pandemic. Health fiqh provides the legal basis for various efforts made in handling the pandemic, such as isolation, quarantine, social restrictions and vaccination. Based on the research results, it can be concluded that the integration of health fiqh in handling the Covid-19 pandemic is important. This is because health fiqh can contribute to providing a legal basis for various efforts made in handling the pandemic.